Determinants of Dropout and Child School Enrollment: A Case Study from Rural Islamabad - Naz, Uzma; Ejaz, Zainab; Khan, Naveed (Journal of Quantitative Methods, 2019)
Education is an important pillar for the development of any society. Generally, school enrollment in developing countries is observed very low compared to the developed countries and the situation is further worsened by the high dropout rate. The current study investigates the major factors responsible for high dropouts in Islamabad, Pakistan, particularly in rural areas. For this purpose, the primary data have been obtained through a detailed questionnaire collecting information on child socioeconomic, household, cultural, and other characteristics. For modeling purposes, Probit model is used to investigate the effects of various factors on high child dropout rate. The results revealed that besides the distance from school to home, financial constraints are the most important reason for dropping out. Moreover, the education of father, age of the child and the gender of the child are also highly significant variables that determine the probability of a child dropout.